On the uniqueness of representation by linear superpositions - Ismailov, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
Let $Q$ be a set such that every function on $Q$ can be represented by linear superpositions. This representation is, in general,not unique. However, for some sets, it may be unique provided that the initial values of the representing functions areprescribed at some point of $Q$. We study the properties of these sets.